2017
DOI: 10.1073/pnas.1612991114
|View full text |Cite
|
Sign up to set email alerts
|

SGK3 sustains ERα signaling and drives acquired aromatase inhibitor resistance through maintaining endoplasmic reticulum homeostasis

Abstract: Many estrogen receptor alpha (ERα)-positive breast cancers initially respond to aromatase inhibitors (AIs), but eventually acquire resistance. Here, we report that serum-and glucocorticoid-inducible kinase 3 (SGK3), a kinase transcriptionally regulated by ERα in breast cancer, sustains ERα signaling and drives acquired AI resistance. SGK3 is up-regulated and essential for endoplasmic reticulum (EnR) homeostasis through preserving sarcoplasmic/EnR calcium ATPase 2b (SERCA2b) function in AI-resistant cells. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…In support of our view, other studies have demonstrated that activated GR preferentially suppresses the function of AP-1 family members (39,40). In addition, synergistic upregulation of SGK1 expression by E 2 and dexamethasone facilitates maintenance of the homeostasis in the endoplasmic reticulum to antiapoptosis (41,42). All of these findings suggest that activated GR is a potent regulator of multiple stress-responsive transcription factors, thereby modulating stress and inflammatory responses.…”
Section: Discussionsupporting
confidence: 86%
“…In support of our view, other studies have demonstrated that activated GR preferentially suppresses the function of AP-1 family members (39,40). In addition, synergistic upregulation of SGK1 expression by E 2 and dexamethasone facilitates maintenance of the homeostasis in the endoplasmic reticulum to antiapoptosis (41,42). All of these findings suggest that activated GR is a potent regulator of multiple stress-responsive transcription factors, thereby modulating stress and inflammatory responses.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, a novel function of PERK was described 46 , 47 as a structural tether to increase the proximity of contact sites between the endoplasmic reticulum and mitochondria, which may facilitate oxidative stress. Nevertheless, how PERK actually modulates these stress-responsive transcription factors is various, which depends on the extent of PERK activation and different cell context 48 . All of these findings support the conclusion that PERK plays a central role to convey both adaptive and apoptotic signals from the endoplasmic reticulum to the nucleus 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although combining lapatinib and PI3K inhibitors could be limited by toxicity (71), targeting pathway rewiring could prove beneficial. SGK3 is an estrogen receptor target gene (72,73), but less is known about the role of ER-SGK3 axis in cancer. Comporting with previous reports that SGK1 or SGK3 can mediate AKT-independent activation of mTORC1 and survival in cancer cells treated with PI3K⍺-specific or AKT inhibitors (38,42), our data implicate SGK3 as a key ER target that mediates survival in response to HER2 inhibition in luminal-like DTPs.…”
Section: Discussionmentioning
confidence: 99%